Characterization of a Mycoplasma pneumoniae hmw3 Mutant: Implications for Attachment Organelle Assembly - Willby, Melisa J. (American Society for Microbiology, 2002)
The proteins required for adherence of the pathogen Mycoplasma pneumoniae to host respiratory epithelial cells are localized to a polar structure, the attachment organelle. A number of these proteins have been characterized functionally by analysis of noncytadhering mutants, and many are components of the mycoplasma cytoskeleton. Mutations in some cytadherence-associated proteins have pleiotropic effects, including decreased stability of other proteins, loss of adherence and motility, and abnormal morphology. The function of protein HMW3, a component of the attachment organelle, has been difficult to discern due to lack of an appropriate mutant. In this paper, we report that loss of HMW3 resulted in decreased levels and more diffuse localization of cytoskeletal protein P65, subtle changes in morphology, inability to cluster the adhesin P1 consistently at the terminal organelle, reduced cytadherence, and, in some cells, an atypical electron-dense core in the attachment organelle. This phenotype suggests a role for HMW3 in the architecture and stability of the attachment organelle.